1992
DOI: 10.1007/bf00194311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the gene for the human vitamin-D-binding protein (group-specific component): allelic differences of the common genetic GC types

Abstract: DNA sequence analysis of the polymerase chain reaction products, including the coding region for amino acids 416 and 420, of the vitamin-D-binding protein (DBP, group-specific component, GC) shows allele-specific differences. The GC2 and GC1F phenotypes have an aspartic acid residue at amino acid position 416, whereas the GC1S phenotype has a glutamic acid at this position. In the GC2 phenotype, amino acid 420 is a lysine residue, and in the both common GC1 phenotypes, it is a threonine residue. The nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 21 publications
2
74
1
1
Order By: Relevance
“…The frequency of homozygotes for this haplotype was similar in all three groups: 3.0% (n ¼ 5) in controls, 3.3% (n ¼ 6) in type 1 patients, and 1.9% (n ¼ 4) in type 2 patients. Thus the frequencies of this variant were similar in all our groups and similar to the published data on white populations (18).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency of homozygotes for this haplotype was similar in all three groups: 3.0% (n ¼ 5) in controls, 3.3% (n ¼ 6) in type 1 patients, and 1.9% (n ¼ 4) in type 2 patients. Thus the frequencies of this variant were similar in all our groups and similar to the published data on white populations (18).…”
Section: Resultssupporting
confidence: 91%
“…Thus it is possible that the effect of these variants of the DBP gene on the development of type 2 diabetes is peculiar to non-whites. It is interesting that the prevalence of homozygotes for the Asp-Thr haplotype, previously reported to be associated with quantitative prediabetic traits, is about seven to eight times greater in Pima Indians than in white populations (9,18).…”
Section: Discussionmentioning
confidence: 92%
“…Among several genetic variants of GC, rs7041 and rs4588, in exon 11, led to a Glu/Asp amino acid change at codon 416 and a Thy/Lys amino acid change at codon 420 [35], respectively. These two SNPs are the most commonly studied and repeatedly reported to be associated with lower levels of 25(OH)D. Our finding is in line with the results of several [11,17,19,23,31], but not all [12], recent studies that investigated the association between the genetic variants of GC and vitamin D. In a study of 3,210 Han Chinese from Beijing and Shanghai, Lu et al [11] found that the risk alleles of GC-rs2282679, rs4588 and rs7041 were significantly associated with lower levels of plasma 25(OH)D. The haplotype that contained all three risk alleles, and the C allele of rs1155563 was associated with lower levels of plasma 25(OH)D when compared with the haplotype that carried the four protective alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The three most common variants of DBP (also known as GC globulin) are GC1F, GC1S, and GC2. Each variant is characterized by a different combination of two single nucleotide polymorphisms (rs4588 and rs7041) resulting in two amino acid substitutions and differing glycosylation patterns (17). (Table 1, Figure 1).…”
Section: Introductionmentioning
confidence: 99%